Implementation of Warm Moringa Leaf Compress Therapy to Reduce Pain in Clients with Gout Arthritis - Maria Diana Tia; Pasionista Vianitati; Adriana Fonseca da Silva (Universitas Duta Bangsa Surakarta, 2026)
Gout arthritis, or uric acid, is a disease that affects the joint system, caused by factors such as age, gender, medical history, and obesity. A warm compress using moringa leaves, which contain low molecular weight flavonoids, allows the compounds to easily dissolve in water and be absorbed by the skin's pores. This can lead to vasodilation (expansion of blood vessels), which improves blood flow to the painful areas of the body. The aim of this study was to reduce pain experienced after health education and demonstration. Method the research used a case study method with two respondents in the Kota Uneng Subdistrict. The results from the case study showed that the application of warm moringa leaf compresses for 4 days successfully reduced pain in both patients with gout arthritis. Both clients were able to control their pain and independently perform the moringa leaf warm compress therapy. Therefore, the warm compress therapy with moringa leaves has been proven effective in reducing pain in gout arthritis patients.